ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERHADAP TERJADINYA PENYAKIT JANTUNG KORONER DI POLI JANTUNG RSUD PIRNGADI MEDAN TAHUN 2017 - Siti Aisyah Safrul; Daniel Ginting; Janno Sinaga (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Various risk factors are suspected to encourage the occurrence of CHD, some may be modified but some are not. The purpose of this study is to analyze the factors that affect the occurrence of Coronary Heart Disease In Cardiovascular Poly Pirngadi Medan Year 2017. Case population in this study is all heart patients Coroner who came to treatment at Pirngadi Hospital 2017 in 2017 amounted to 491 people. From the results of this calculation then the researchers set the number of samples as many as 83 people. The results showed that there was Based on the results obtained that the sex effect on coronary heart events with p value = 0.023, age affects coronary heart events, Smoking Habit affect coronary heart events. Hypertension to coronary heart events. Diabetes (DM) against coronary heart events. Obesity has an effect on coronary heart event. Physical activity has an effect on coronary heart event. Suggested efforts to prevent non-communicable diseases, especially coronary heart disease in women more useful done from adolescence, so that risk factors can be controlled early, especially controlling obesity and healthy diet through physical activity and healthy diet; high fiber, low fat, low salt and sugar.Keywords: Factors Affecting Against Coronary Heart Disease